Analysis of Banking Criminal Cases Based on The Perspective of Law Number 10 of 1998 Concerning Banking - Manu Kepakisan, I Gusti Agung; Walesa Putra, I Made (West Science Interdisciplinary Studies, 2025)
This study aims to analyze banking crimes based on the perspective of Law Number 10 of 1998 concerning Banking with a focus on cases of embezzlement of customer funds by bank employees. The method used is a literature study through a review of laws and regulations, scientific journals, articles, and related court decisions. The case of the loss of customer funds in the name of Sigit Prasetya at Bank BRI is the main focus in analyzing the elements of the crime and the relevant forms of legal responsibility. The results of the analysis show that banking crimes often occur due to the weak implementation of the principle of prudence and internal bank supervision. Although the main perpetrators are individual bank employees, civil liability can still be directed at the bank as a corporation. This emphasizes the importance of strengthening regulation and supervision in maintaining public trust in the banking system.